2015
DOI: 10.1186/s12884-015-0747-1
|View full text |Cite
|
Sign up to set email alerts
|

Changes in detection of birth defects and perinatal mortality after introduction of prenatal ultrasound screening in the Kola Peninsula (North-West Russia): combination of two birth registries

Abstract: BackgroundPrenatal diagnostics ultrasound was established in Russia in 2000 as a routine method of screening for birth defects. The aims of the current study were twofold: to assess changes in birth defects prevalence at birth and perinatal mortality after ultrasound screening was implemented and to estimate prenatal detection rates for congenital malformations in the city of Monchegorsk (Murmansk County, North-West Russia).MethodsThe Murmansk County Birth Registry and the Kola Birth Registry were the primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 19 publications
2
8
0
Order By: Relevance
“…The overall PDR was 50.3%. This rate is within the range previously reported in other settings: 34.9-62.0% (Rydberg and Tunón 2017;Postoev et al 2015;Rossi and Prefumo 2013;CAROBB 2012;Campaña et al 2010). Birth in an institution belonging to the nonpublic sector was shown to be a predictor for a higher chance of prenatal detection.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The overall PDR was 50.3%. This rate is within the range previously reported in other settings: 34.9-62.0% (Rydberg and Tunón 2017;Postoev et al 2015;Rossi and Prefumo 2013;CAROBB 2012;Campaña et al 2010). Birth in an institution belonging to the nonpublic sector was shown to be a predictor for a higher chance of prenatal detection.…”
Section: Discussionsupporting
confidence: 86%
“…European surveillance programs showed the influence on PDR of different legislations regarding mandatory fetal screening of CA. Countries without mandatory prenatal screening had the lowest rates (Postoev et al 2015;Stoll et al 2001;Garne et al 2005). Likewise, in the Swedish experience, the routine use of a checklist to investigate CA prenatally increased prenatal detection (Rydberg and Tunón 2017).…”
Section: Discussionmentioning
confidence: 98%
“…In our previous study (Postoev et al, 2015b), the prenatal detection rate for CAKUTs in Monchegorsk was 42.1% for the 2000-2007 period. The possibility for underestimating the prevalence when using data at birth is illustrated by Caiulo et al, 2012, who showed that the prevalence of CAKUTs among children at the age of two months was close to 1 % based on mass ultrasound screening.…”
Section: Prevalence Of Cakutsmentioning
confidence: 83%
“…Serial ultrasonic scanning has been recommended in the national and international ANC standards as a means to detect foetal growth abnormalities [ 4 , 24 , 25 , 38 , 41 , 49 ]. However, the fields to record such measurements do not exist in the manual pregnancy register ( Table 12 ).…”
Section: Discussionmentioning
confidence: 99%